Predictive value of the systemic immune-inflammation index for cancer-specific survival of osteosarcoma in children - Ouyang, Haiping; Wang, Zhongliang (Frontiers in Public Health, 2022)
Background Osteosarcoma (OS) is the primary malignant bone tumor that most commonly affects children and adolescents. Recent years effective chemotherapy have improved the 5-year survival in osteosarcoma patients to up to 60%-70%. Still, there is a lack of novel therapeutic strategies to enhance further survival. Our study aimed to evaluate the clinical significance of pretreatment inflammatory-based parameters, including PLT, NLR, and SII, as prognostic indicators of survival in pediatric osteosarcoma patients. Methods A total of 86 pediatric osteosarcoma patients between 2012 and 2021 in the Department of Orthopedics or tumor Surgery of Children's Hospital affiliated to Chongqing Medical University were retrospectively analyzed. The clinicopathological variables and systematic inflammatory biomarkers, including NLR, PLR and SII, was performed by the A Receiver operating characteristic (ROC) curve and Cox proportional risk regression model. According to the results of multivariate analysis, a prognostic nomogram was generated, and the concordance index (C-index) was calculated to predict the performance of the established nomogram. The survival curve was plotted by the Kaplan-Meier method. Results Univariate analysis showed that TNM stage, tumor size, NLR value, PLR value, SII value, neutrophil count and platelet count were related to CSS (p < 0.05). According to multivariate analysis, only TNM stage (p = 0.006) and SII values (p = 0.015) were associated with poor prognosis.To further predict survival in pediatric osteosarcoma patients, multivariate Cox regression analysis was used to predict cancer-specific survival at 1, 3 and 5 years. And constructed a nomogram model to predict children's CSS. The C-index of the nomogram is 0.776 (95%CI, 0.776–0.910), indicating that the model has good accuracy. Conclusion Preoperative SII and TNM staging are independent prognostic markers for pediatric osteosarcoma patients. SII may be used in conjunction with TNM staging for individualized treatment of pediatric osteosarcoma patients in future clinical work.